Intraoperative plethysmography variability index directed fluid management versus standard care during intraabdominal surgery in cancer patients - Pardeep Kumar; Asthana, Unnati; Shweta Bhardwaj; Jai Prakash Rohilla (Asian Journal of Medical Sciences, 2023)
Background: During the past 20 years, numerous publications have described the usefulness of systolic pressure variation, pulse pressure variation, stroke volume variation, etc., to guide intraoperative fluid administration. However, we still lack robust noninvasive physiological variables to successfully predict the response to fluid loading. Aims and Objectives: The present study was designed to evaluate the utility of plethysmography variability index (PVI) to optimize fluid management during intra-abdominal surgery in cancer patients. Materials and Methods: After the Institutional Ethics Committee approval and consent, 60 patients scheduled for elective lower abdominal cancer surgeries were randomized to receive fluid by either PVI-directed management (2 mL/kg/h) or using central venous pressure (8 mL/kg/h) after standardized technique of general and lumbar epidural anesthesia. The PVI was calculated by measuring changes in the PI during the respiratory cycle (PVI = [(PImax - PImin)/PImax] × 100). Arterial blood samples were taken at the time of incision and after 6 h postoperatively. Instances of intraoperative hypotension and oliguria were recorded. Results: Among the 60 patients enrolled in the study, demographic data, ASA status, duration of surgery, and hemodynamics were found to be comparable. The amount of crystalloid given was significantly lesser in Group P (984.70±51.16) as compared to Group C (2395.27±209.68) (P<0.001). Four patients in Group P and three patients in Group C required vasopressors. Conclusion: The use of PVI-guided fluid management was associated with lower lactate levels and crystalloid requirement. Reduced lactate levels in PVI-guided patients suggest that PVI-guided fluid management may be tailored to everyone’s needs.